2000
DOI: 10.1001/archinte.160.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin vs Heparin in the Treatment of Patients With Pulmonary Embolism

Abstract: Low-molecular-weight heparin administered once daily subcutaneously was no less effective and probably more effective than use of dose-adjusted intravenous unfractionated heparin for preventing recurrent venous thromboembolism in patients with PE and associated proximal deep vein thrombosis. Our findings extend the use of low-molecular-weight heparin without anticoagulant monitoring to patients with submassive PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(81 citation statements)
references
References 65 publications
3
66
0
9
Order By: Relevance
“…The cause of this difference remains unclear, although the mortality benefit of LMWH appears restricted to the subgroup of patients with VTE associated with malignancy. 29,30 Subsequent to publication of these meta-analyses, randomized trials confirmed that LMWH is at least as effective and safe as UFH for treatment of VTE, [31][32][33] and once-daily LMWH was as effective and safe as UFH for treatment of symptomatic PE. 34 The predictable anticoagulant response to weight-based LMWH allows for outpatient therapy of VTE.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…The cause of this difference remains unclear, although the mortality benefit of LMWH appears restricted to the subgroup of patients with VTE associated with malignancy. 29,30 Subsequent to publication of these meta-analyses, randomized trials confirmed that LMWH is at least as effective and safe as UFH for treatment of VTE, [31][32][33] and once-daily LMWH was as effective and safe as UFH for treatment of symptomatic PE. 34 The predictable anticoagulant response to weight-based LMWH allows for outpatient therapy of VTE.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…12,13 Three other articles [14][15][16] had follow-up publications reporting the cancer subgroup data. [17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies. [30][31][32][33][34][35][36][37][38][39] Thus, of 24 studies with cancer patients' subgroups, we were able to obtain data for 13 studies.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…As HBPM têm substituído a heparina não fracionada por possuírem menos efeitos indesejáveis como a resposta variável devido à ligação com proteínas plasmáticas ou a trombocitopenia induzida pela heparina (TIH) [1]. Além disso, diversos estudos realizados com modelos de trombose venosa em animais e estudos clínicos em humanos portadores de doenças venosas tromboembólicas mostraram que as HBPM são equivalentes ou até mesmo superiores à heparina não fracionada em relação ao seu efeito antitrombótico e possuem maior segurança por apresentar menor risco hemorrágico [5,14,17,18,19,20,21,22].…”
Section: Antitrombóticosunclassified